Проблеми перекладу при укладанні навчального італійсько-українського словника - Калинчук, Д. (Лексикографічний бюлетень, 2006)
Composing lerner’s dictionary has many difficulties of translation. Hence, not only the
lexicographical principles should be used but also the rules of translation.